ANALISA PENGENDALIAN KUALITAS PRODUK KABEL NFA2X DENGAN MENGGUNAKAN METODE NEW SEVEN TOOLS UNTUK MEMINIMALKAN DEFECT DI PT. PRIMA CABLE INDO - yudi maulana (Universitas Pamulang, 2021)
PT. Prima Cable Indo is a company that produces electric cable. The quality of the product is very important to maiantain a customer satisfaction, and qualiy control is a must for PT. Prima Cable Indo. Quality control is a requirement to ensure that the product meets the conformity of the estahabilished standard. Research conducted at PT. Prima Cable Indo aimz to minimize the number of defective products resulting from the production process, especially for the NFA2X cable type. PT.Prima Cabale Indo applies the new seven tools in controlling quality, consists of some steps which are affinity diagram, interrelationship diagram, matrix diagram, matrix data analysis, and tree diagram. The failures found in NFA2X cable among others are breakdown voltage, rough cable surface, loosened cable strands, and insulation is not center. The result finds some factors that cause the defect of NFA2X cable are the workers, materials, machine, environment, and method.